2018 GFPR Moscow - Tarasov, Vladimir (2018)
Special Event 2018 Global Food Policy Report - Moscow, Russia Organized by Eurasian Center for Food Security (ECFS) at the Lomonosov Moscow State University (MSU), International Food Policy Research Institute (IFPRI), Faculty of Economics of the MSU and the World Bank May 30, 2018 - 10:00 am to 11:20 am MSK Prof. Vladimir Tarasov